THE IMPORTANCE OF TRADEMARKS FOR SELLERS ON TIKTOK SHOP & SHOPEE - Fatimah Raudhatuz Zahra; Muhammad Khoirul Anwar Lubis; Nurjanna Dongoran; Singgih Al Ghifary (Academic Solution Publisher, 2025)
The rapid growth of e-commerce platforms such as TikTok Shop and Shopee has created significant opportunities for entrepreneurs to expand their market reach and boost sales. However, in the midst of intense competition, a registered trademark becomes a critical factor in distinguishing one seller from another. The core issue addressed in this study is the lack of awareness among many sellers about the importance of trademark registration and protection, which can lead to brand disputes or identity theft. This study aims to analyze the strategic role of trademarks in building consumer trust and increasing product value on these two digital platforms. A descriptive qualitative approach was employed, using case studies of 10 active sellers on TikTok Shop and Shopee. Data were collected through in-depth interviews, observation of branding activities, and documentation of shop profiles. The findings indicate that sellers with registered trademarks and consistent branding strategies are more likely to attract consumers, gain customer loyalty, and enjoy legal protection for their products. In contrast, sellers without trademarks often struggle to build market trust and are more vulnerable to product imitation. In conclusion, a trademark serves not only as a business identity but also as a strategic asset that significantly impacts the sustainability and growth of online sellers in the digital era. Therefore, it is crucial for online entrepreneurs to understand and apply trademark protection from the outset of their business journey.